Pills, Potions, and Poisons: Interdisciplinary Public Engagement Opportunities Inspired by a 17th Century Apothecary - Helen Cooke (17199169) (2025)
The transcript of the inventory of the contents of a 17th century apothecary’s shop was discovered during research for a museum exhibition on health and disease through the ages. This led to research into the remedies dispensed by the apothecary, which provided the impetus for development of public-engagement deliverables, including interdisciplinary talks, chemistry demonstrations, a searchable record of the contents of the inventory, and production of an accessible local-history booklet. The approach taken used history as a gateway to introduce chemistry and inspire people of all ages to engage with science. Detailed instructions are provided for four striking chemical demonstrations centered around apothecaries and exploiting some of the substances present in the inventory.